2005
DOI: 10.1002/ejic.200500464
|View full text |Cite
|
Sign up to set email alerts
|

Metal Binding Within a Peptide‐Based Nucleobase Stack with Tuneable Double‐Strand Topology

Abstract: Peptide nucleic acid (PNA) oligomers with linear topology are synthesised with histidines at the central positions in order to provide metal-ion coordination sites within the water shielded and non-polar environment of a nucleobase stack that emerges upon duplex formation. Variation of the linker length used for attachment of the nucleobases to the regular peptide backbone allows for fine tuning of the distances and coordination environment at the metal binding site. The effect of zinc and copper incorporation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…150 In a similar line of thought, Diederichsen, Meyer and coworkers have reported the insertion of two successive histidines into the central position of various alanyl-PNA oligomers (alanyl-PNAs). 151 Once hybridised to a complementary alanyl-PNA strand also containing two successive histidines, they found that the addition of Zn 2+ significantly enhanced the double-strand stability, thus supporting the coordination of Zn 2+ by the histidine-N and the incorporation of the metal ion within the base stack. 151 However, in contrast to Zn 2+ , Cu 2+ ions did not induce double-strand formation.…”
Section: Modulation Of Pna•dna Hybrid Stability Using Metal Complexesmentioning
confidence: 92%
See 1 more Smart Citation
“…150 In a similar line of thought, Diederichsen, Meyer and coworkers have reported the insertion of two successive histidines into the central position of various alanyl-PNA oligomers (alanyl-PNAs). 151 Once hybridised to a complementary alanyl-PNA strand also containing two successive histidines, they found that the addition of Zn 2+ significantly enhanced the double-strand stability, thus supporting the coordination of Zn 2+ by the histidine-N and the incorporation of the metal ion within the base stack. 151 However, in contrast to Zn 2+ , Cu 2+ ions did not induce double-strand formation.…”
Section: Modulation Of Pna•dna Hybrid Stability Using Metal Complexesmentioning
confidence: 92%
“…151 Once hybridised to a complementary alanyl-PNA strand also containing two successive histidines, they found that the addition of Zn 2+ significantly enhanced the double-strand stability, thus supporting the coordination of Zn 2+ by the histidine-N and the incorporation of the metal ion within the base stack. 151 However, in contrast to Zn 2+ , Cu 2+ ions did not induce double-strand formation. The authors suggested that this difference could be explained by the different geometric preferences of Zn 2+ .…”
Section: Modulation Of Pna•dna Hybrid Stability Using Metal Complexesmentioning
confidence: 92%
“…Even if focussing only on the use of artificial nucleosides, examples exist for DNA duplexes containing one or two metal-mediated base pairs interspersed between natural ones, 6-8 DNA double helices with continuous stretches of metalated base pairs, 9-11 and DNA duplexes with different metalmediated base pairs at pre-defined positions. 12 When including also metal-mediated base pairs from natural nucleosides, 13-15 even more combinations can be envisaged.In addition to DNA, other nucleic acids such as RNA, 16 GNA 17 or PNA 18,19 have been modified with metal-mediated base pairs, too. Experimentally derived structural information on such metal-mediated nucleic acids is very scarce: only one DNA double helix comprising two non-neighbouring metal-mediated base pair has been structurally characterized as yet.…”
mentioning
confidence: 99%
“…In addition to DNA, other nucleic acids such as RNA, 16 GNA 17 or PNA 18,19 have been modified with metal-mediated base pairs, too. Experimentally derived structural information on such metal-mediated nucleic acids is very scarce: only one DNA double helix comprising two non-neighbouring metal-mediated base pair has been structurally characterized as yet.…”
mentioning
confidence: 99%
“…The artificial nucleobases are a) 5Ј-methyl-2,2Ј-bipyridine; [76] b) 2,2Ј-bipyridine; [78] c) 4Ј-methyl-2,2Ј-bipyridine; [80] d) 8-hydroxyquinoline; [77] e) 4Ј-phenyl-2,2Ј:6Ј,2ЈЈ-terpyridine; [81] f) imidazole. [79] R indicates the point of attachment to the peptide backbone.…”
Section: Metal-ion-mediated Base Pairs With Artificial Nucleosidesmentioning
confidence: 99%